2005
DOI: 10.1007/s10750-004-5711-4
|View full text |Cite
|
Sign up to set email alerts
|

Toward using Margaritifera falcata as an indicator of base level nitrogen and carbon isotope ratios: insights from two California Coast Range rivers

Abstract: Measurements of freshwater mussel tissue are potentially very useful for determining base-level isotopic values for food web studies in aquatic environments. As long-lived, filter-feeding organisms, mussels have the potential to spatially and temporally average the isotopic baseline signal. Following from earlier studies that focused on lake environments, this study investigates the stable carbon and nitrogen isotope ratios in tissue of the river dwelling freshwater mussel, Margaritifera falcata, in two extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…riffle and pool derived algae, with relatively depleted and enriched carbon, respectively as shown by Finlay et al 1999) and/or possibly terrestrial sources. Lamprey tissue values were similar to Margaritifera tissue δ 13 C and δ 15 N values (−22.9‰, 2.6‰, respectively) reported by Howard et al (2005) during the summer period in the South Fork of the Eel River. Finlay et al (1999) report summer δ 13 C values in the South Fork of the Eel River of −17.9‰ for epilithic algae in pool habitats, −26.2‰ for epilithic algae in riffle habitats, and −27.5‰ for terrestrial detritus.…”
Section: Discussionsupporting
confidence: 83%
“…riffle and pool derived algae, with relatively depleted and enriched carbon, respectively as shown by Finlay et al 1999) and/or possibly terrestrial sources. Lamprey tissue values were similar to Margaritifera tissue δ 13 C and δ 15 N values (−22.9‰, 2.6‰, respectively) reported by Howard et al (2005) during the summer period in the South Fork of the Eel River. Finlay et al (1999) report summer δ 13 C values in the South Fork of the Eel River of −17.9‰ for epilithic algae in pool habitats, −26.2‰ for epilithic algae in riffle habitats, and −27.5‰ for terrestrial detritus.…”
Section: Discussionsupporting
confidence: 83%
“…3 plots data from modern plant and animal samples amalgamated from a wide range of studies in and around Suisun Marsh, including San Francisco Bay and the California Delta (data assembled from Bartelink, 2006;Canuel et al, 1995;Cloern et al, 2002;Goldberg, 1993;Greenfield et al, 2002;Grenier et al, 2002;Howard et al, 2005;Howe and Simenstad, 2011;Kleckner et al, 2010; Newsome et al, 2009Newsome et al, , 2012Rast, 1989;Sarakinos et al, 2002;Sydeman et al, 1997). Given large inputs of fertilizer and sewage into modern waterways, and extreme changes to the local ecology, especially the effects of invasive species, it is difficult to estimate how applicable modern data are to reconstructing ancient foodwebs in Central California (Wankel et al, 2006).…”
Section: Modern Foods Near Suisun Marshmentioning
confidence: 99%
“…All food source samples were treated with 0.1 N HCl to remove inorganic carbon and then dried at 60°C for more than 24 h. The foot muscle of snails and the adductor muscle of bivalves were resected and dried at 60°C for more than 24 h. Howard et al (2005) showed that the d 15 N value of mussels increased by approximately 2& with increasing age. In order to examine the relationship between body size and isotope signatures, we compared the dry weight of soft tissues and isotope signatures of macroinvertebrates for sampling sites at which more than three individuals were collected.…”
Section: Sample Collection and Stable Isotope Analysismentioning
confidence: 99%